2023
DOI: 10.1007/s00784-023-04965-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone area in the posterior region for mandibular molar distalization in class I and class III patients

Abstract: The aim of this study was to investigate the bone area in the posterior region, which is important for mandibular molar distalization in skeletal Class I and Class III individuals with normodivergent and hyperdivergent vertical growth patterns. Materials and MethodsIn this study, cone-beam computed tomography scans of 120 individuals divided into 4 groups as Class I normodivergent (Group-I), Class I hyperdivergent (Group-II), Class III normodivergent (Group-III) and Class III hyperdivergent (Group-IV). Retromo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…By evaluating the quality of the mandibular bone, clinicians can identify potential challenges, develop appropriate treatment plans, and minimize the risk of complications during the distalization process [18,19]. Several studies revealed that the success of this procedure heavily relies on the assessment of the mandibular bone's quality, as it directly influences the stability and efficiency of the distalization process [8,20].…”
Section: Introductionmentioning
confidence: 99%
“…By evaluating the quality of the mandibular bone, clinicians can identify potential challenges, develop appropriate treatment plans, and minimize the risk of complications during the distalization process [18,19]. Several studies revealed that the success of this procedure heavily relies on the assessment of the mandibular bone's quality, as it directly influences the stability and efficiency of the distalization process [8,20].…”
Section: Introductionmentioning
confidence: 99%